POTENSI BESAR BISNIS PENUKARAN VALUTA ASING ”MONEY CHANGER” - Ferdi Pratama Putra; Anggoro Purwanto; Winardi; Besar Agung Martono (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
Foreign exchange is a service to exchange foreign currency, given to people or company who wants to buy or sell a currency by money changer. Jakarta as the capital city ofIndonesia is one of the promising regions to build a foreign exchange business because many companies used foreign currencies for transactions, large numbers of foreign currencies need in similar companies, Jakarta has many tourist destinations, and local residents’ activity that travel to other country. Also, development in technology encourages companies to innovate in improving services. To prove that this business is feasible, a business feasibility analysis is needed to selected aspects, which is environmental aspect,legal aspect, technical and technological aspect, HR (Human Resources) aspect, marketing aspect, and financial aspect. Environmental aspect is feasible because of its strategic and promising location. Legal aspect is feasible because the needs of documents and licensing requirements that are met. The technical and technological aspect is feasible because of the innovation in service. HR aspect is feasible because of the organizational structure andreadiness of skilled workforces. Marketing aspect is feasible because of the market of thebusiness. Financial aspect is feasible because of indications of valuation to produce aforeign exchange business.